A pseudo-consecutive non-canonical serial verb construction in isiXhosa - Andrason, Alexander (Stellenbosch Papers in Linguistics Plus, 2018)
This snippet contributes to the study of less canonical Serial Verb Constructions (SVCs) of a multi-clausal consecutive origin. The author demonstrates that the BUYA gram in isiXhosa constitutes an example of a pseudo-consecutive non-canonical SVC. Although BUYA complies with most features postulated for the prototype of a SVC, it also exhibits formal marking of consecutivisation. Nevertheless, as the gram does not comply with the various properties exhibited by consecutive patterns in isiXhosa, this marking is dummy.